The Role of Digital Forensics in Combating Cybercrimes - Harbawi, Malek; Varol, Asaf (Ieee, 2016)
The recent development in Information Communication Technology (ICT) has made changes in every aspect in our life. These changes are clearly reflected in cyberspace-related areas. The positive influence of cyberspace on knowledge, trade and business, and communication is undoubtable. However, there is a dark side of cyberspace deteriorates its peaceful usage that is cybercrimes. Cybercrimes arc defined as any illegal activities practiced by or done via cyberspace and its electronic environment. Unlike traditional crimes, cybercrimes present a real dilemma due to the fact that criminals' identity may be hidden or fraud in virtual domain. The concept of digital forensics have come to the existence in an attempt of formulating possible ways for cybercrimes investigation and analysis process. In this paper, we deplore the concept of digital forensics in the context of cybercrimes. An investigation of the positive impact of digital forensics in combating cybercrimes is discussed and useful remarks on open research issues are provided for further investigation activities.
4th International Symposium on Digital Forensic and Security (ISDFS) -- APR 25-27, 2016 -- Little Rock, AR
Keywords: cybercrime; digital forensics; cyber-attacks; digital forensics tools; technology gap